Prevalence of feline viral leukemia in Moscow and the Moscow Oblast with the analysis of hematological and biochemical blood parameters - A. P. Zenchenkova (Ветеринария сегодня)
Feline viral leukemia is an infectious disease that is common throughout the world. Despite the statistical records that have been successfully kept in other countries for many years, there is little data on the prevalence of the infection in the Russian Federation, and the samples are represented by a small number of animals. 11,807 blood samples collected in Moscow and the Moscow Oblast were tested for FeLV antigen and antibodies against FeLV by polymerase chain reaction, enzyme immunoassay, and immunochromatographic assay. The prevalence of feline viral leukemia was 12.8%, which correlates with the prevalence of the disease detected in developing countries, and speaks of a high disease prevalence in domestic cats in Moscow and the Moscow Oblast. Most often, feline leukemia virus was detected in free roaming domestic cats. During the diagnostic studies, the following hematological abnormalities were found: anemia, thrombocytopenia, lymphopenia, and a shift of the leukocyte formula to the left. Biochemical blood tests showed the increased levels of total protein, aspartate aminotransferase, alkaline phosphatase, and C-reactive protein. The obtained data demonstrate non-specific hematological and biochemical abnormalities in infected cats, and dictate the need for further study of the risk factors that predispose cats to the infection with this viral disease. Feline viral leukemia should be suspected in case of a non-specific clinical picture, as well as in case of abnormalities in blood biochemical and hematological parameters of free roaming cats or of those which have had a confirmed contact with their conspecifics.